Analisis Struktur Pasar Strategi Untuk Menghadapi Persaingan Usaha Agrowisata Amanah, Karangpandan Karanganyar: Analisis Struktur Pasar Strategi Untuk Menghadapi Persaingan Usaha Agrowisata Amanah, Karangpandan Karanganyar - Wahyu Puji Lestari; Rahmawati Setiyani; Sugeng Edi Waluyo (Universitas Duta Bangsa Surakarta, 2026)
Business competition is a natural occurrence in any market. The decline in tourist visits and revenues occurred due to the emergence of similar competitors in Karanganyar Regency. This study was conducted to analyze effective marketing strategies to address this competition, thereby increasing tourist visits and agrotourism revenue. Amanah Agrotourism is an agricultural-based educational tourism destination, enhancing tourists' knowledge and experience. The purpose of this study was to understand the competitive conditions faced by Amanah Agrotourism. This study utilized primary and secondary data. Some data were generated through observation and interviews with respondents. Respondents were selected using purposive sampling. This study employed market structure analysis. Market structure analysis is conducted to evaluate companies' interactions, competition, pricing, and market share. The results of the market structure analysis at Amanah Agrotourism indicate that Amanah Agrotourism has 11 competitors similar to Amanah Agrotourism. Based on the market share analysis, Amanah Agrotourism has a market share that focuses only on a small segment and has not yet dominated the entire market.